PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO PINK KOTA PAREPARE - Sartika, Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of price and service quality variables on purchasing decisions. Data collection using a questionnaire instrument. The research sample was 300 respondents. The data analysis technique used is multiple linear regression analysis. The results showed that the price variable regression coefficient (X1) with a positive coefficient sign. The significant value of 0.000 is smaller than the significance value of α, namely 0.05. The service quality variable regression coefficient has a positive effect on purchasing decisions with a significant value of 0.000 less than 0.05. The results of all tests concluded that the variable price and service quality had a significant effect on purchasing decisions.